2017
DOI: 10.1161/atvbaha.117.308611
|View full text |Cite
|
Sign up to set email alerts
|

ATVB Distinguished Scientist Award

Abstract: Objective Immune cells play a critical role in atherosclerosis. Co-stimulatory and co-inhibitory molecules of the tumor necrosis factor receptor and CD28 immunoglobulin superfamilies shape T cell and B cell responses, but also have a major effect on antigen presenting cells and non-immune cells. Approach and Results Pharmacological inhibition or activation of co-stimulatory and co-inhibitory molecules as well as genetic deletion demonstrated their involvement in atherosclerosis. This review highlights recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 218 publications
(224 reference statements)
0
12
0
Order By: Relevance
“…Costimulatory molecules such as Cd86 and Cd40 relevant to antigen presentation were also represented among both in vivo M1(=LPS+)C57BL/6J and in vitro classically activated (LPS+IFN-γ) Mφ signatures (2931). CD86 is a ligand for CD28 and is a known inflammatory Mφ/DC marker (32).…”
Section: Analysis Criteria Of In Vivo and In Vitro Signatures And Ovementioning
confidence: 99%
“…Costimulatory molecules such as Cd86 and Cd40 relevant to antigen presentation were also represented among both in vivo M1(=LPS+)C57BL/6J and in vitro classically activated (LPS+IFN-γ) Mφ signatures (2931). CD86 is a ligand for CD28 and is a known inflammatory Mφ/DC marker (32).…”
Section: Analysis Criteria Of In Vivo and In Vitro Signatures And Ovementioning
confidence: 99%
“…T-cell costimulatory or coinhibitory pathways are known to play critical roles in enhancing or inhibiting activation of T cells, respectively. The important costimulatory pathway involving the interactions of B7 ligands CD80 and CD86 on DCs with CD28 on T cells has been suggested to play a dominant role in the modulation of T cell functions and atherosclerosis 7 . A recent study showed that normocholesterolemic CD80 −/− /CD86 −/− or CD28 −/− mice exhibited a marked decrease in Tregs and increased incidence and mortality of angiotensin II-induced AAA 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The T-cell costimulatory and coinhibitory pathways are crucial in modulating functions of Teffs and Tregs and their balance. Recent experimental studies using genetically modified mice or blocking antibodies have revealed that the costimulatory and coinhibitory pathways are critically involved in the pathogenesis of atherosclerosis 7 . Interactions of CD28 on T cells with B7 ligands CD80 and CD86 on antigen-presenting cells are the most important costimulatory pathway for T cell activation 8 .…”
Section: Introductionmentioning
confidence: 99%
“…When T cells are activated, not only is the T cell receptor engaged, but also costimulatory or coinhibitory molecules modulate the response 36,37 . Most studies involving genetic deletion or inhibition of the interaction between the molecular pairs in murine atherogenic models have shown that the costimulatory molecules OX40-OX40L, CD137-CD137L, CD28-CD80/CD86 and CD40-CD40L are proatherogenic and the coinhibitory molecules CTLA4-CD80/CD86, CD27-CD70, and PD-1-PDL1/2 are atheroprotective.…”
Section: T Cell Costimulatory/coinhibitory Moleculesmentioning
confidence: 99%